Research for development volume 3 : a bibliography of staff publications 2002-2005 - Salmon, Frances...[et al.] (UWI. Library MonaJM, 2006)
Captures the published as well as unpublished output of UWI staff. Unpublished material include significant speeches, presentations at conferences and technical reports.